Lemons on Friday : trusting God through my greatest heartbreak - Selecman, Mattie Jackson (W Publishing, 2021)
"How do you go on when life is nothing like what you had hoped it would be? Three weeks before her first wedding anniversary, Mattie Jackson Selecman lost her husband to a traumatic brain injury. Nothing had ever shattered her faith so dramatically. Nothing had ever caused her to question her beliefs or her own identity so deeply. Nothing would transform her so completely. In Lemons on Friday, Mattie offers hope, understanding, and biblical encouragement as you navigate the loss of a loved one, a relationship, or the life you dreamed of living."--Back cover.